Inflammation mechanism and anti-inflammatory therapy of dry eye - Chu, Liyuan; Wang, Caiming; Zhou, Hongyan (Frontiers in Medicine, 2024)
Dry eye is a widespread chronic inflammatory disease that causes fatigue, tingling, burning, and other symptoms. Dry eye is attributed to rheumatic diseases, diabetes, hormone disorders, and contact lenses, which activate inflammatory pathways: mitogen-activated protein kinases (MAPK) and nuclear factor-B (NF-κB), promote macrophage inflammatory cell and T cell activation, and inflammation factors. Clinicians use a combination of anti-inflammatory drugs to manage different symptoms of dry eye; some of these anti-inflammatory drugs are being developed. This review introduces the dry eye inflammation mechanisms and the involved inflammatory factors. We also elucidate the anti-inflammatory drug mechanism and the detection limits.